The Influence of Self Service Technology Toward Customer Satisfaction. Case: Genki Sushi - Susianto, Christie Chandra; Fachira, Ira (Journal of Business and Management, 2015)
Abstract - Companies view technology as a way to enhance service exchanges and has posited that the increasing role of technology in such encounters offers benefits to both customers and firms (e.g, Bitner, Brown, and Meuter 2000; Salomann et al. 2007). GS is one of the businesses that using technology in delivering their restaurant service to gain customer satisfaction. In this case, GS infused Self-Service Technology (SST) that largely replaced their personal service interaction with the customer. SST is a technology infusion, where customers deliver service themselves using some form of technological interface. Technology has replaced the human touch in the process of ordering food, delivering the ordered meal, and billing statement, and in the time customer needs waiter assistance they are able to call the waiter by clicking on the self-service technology device, which also replaced the menu book. Even though companies consider the technologies are able to enhance the service exchange, recent research argued that the technology implementation does not always lead to higher customer satisfaction scores. Therefore, it is important to determine the customer satisfaction of GS services, which remain unidentified. This study aims to explore the influence of SST and Personal Service toward Overall Satisfaction in GS. Quantitative research was conducted in this study by distributing online questionnaires to 100 respondents in Jakarta Selatan that at least had been once to GS, which taken place at Plaza Senayan, Jakarta Selatan. Indicators used in the questionnaire had been proven as valid and reliable using the Pearson correlation and Cronbach Alpha value. Descriptive Analysis and Multiple Linear Regressions (MLR) were conducted to analyze data collected. The research provided empirical evidence of relative impact of SST on overall consumer satisfaction. Findings show that SST positively influence overall satisfaction at GS, however personal service does not have significant influence toward the overall satisfaction, therefore SST considered as the only variable contributive to 21% of the overall satisfaction. This study result shows that Self-Service Technology has enhance service convenience and deliver efficient service process to the customer. The absence of personal service interaction has no direct effect to the overall satisfaction.